THE SMART LIBRARY CONCEPT IN RUSSIAN UNIVERSITY LIBRARIES: THE SYNERGY OF OPEN SCIENCE AND EDUCATION 5.0 - Sokolova, Natalia (Nazarbayev University, 2023)
The concept of “smart library” was put forward and applied by Aittolaet al. of the Oulu University Library in Finland as early as 2003. At that time, “smart” referred to the use of wireless LAN technology in a library to provide users with an electronic map for searching for books, quickly locating the correct bookshelf, and finding the best path to it
Keywords: Type of access: Open Access; SMART Library; Russian University Libraries